ANALISIS USAHATANI DAN PEMASARAN CABAI RAWIT (Capsicum frutescens) DI KECAMATAN BANDAR SEIKIJANG KABUPATEN PELALAWAN PROVINSI RIAU - Ade Alfina; Fahrial (UIR Press, 2024)
This research aims to examine several aspects of cayenne pepper farming, including: (1) the characteristics of entrepreneurs and the profiles of cayenne pepper farmers, (2) cultural technology, utilization of production factors, production costs, output, income, and the efficiency of cayenne pepper farming, and (3) marketing elements, which encompass marketing institutions and channels, marketing functions, costs, margins, profit margins, marketing efficiency, and farmers' share of profits. The study utilized a survey method with a sample size of 40 farmers, and data analysis was performed using descriptive qualitative and quantitative techniques. The findings reveal that (1) the average age of farmers is 37 years, comparable to traders and collectors who are aged 37 and 39 years, respectively. The average educational attainment among these farmers is 11 years, typically completing high school, while the average farming experience is about 6 years; traders and collectors have averages of 4 years and 5 years, respectively. On average, farmers support three family dependents. (2) The production of cayenne pepper stands at 488.70 Garapan/Mt, indicating that the output is below the national production level. However, the income levels of farmers are relatively high due to favorable output and prices, with an average net income of Rp 9,254,416,- Garapan/Mt. Therefore, the cayenne pepper business is considered efficient and viable for further development. (3) In terms of marketing, there are two main channels for cayenne pepper distribution: Channel I involves farmers, collectors, retailers, and consumers, while Channel II consists of farmers, retailers, and consumers. Channel II is more efficient than Channel I. Some marketing institutions do not fulfill all marketing functions. The marketing margin for Channel I is Rp. 5,925/Kg, while Channel II has a margin of Rp. 5,300/Kg. The marketing profit for Channel I is Rp. 3,962.06/Kg, compared to Rp. 4,425.48/Kg for Channel II, indicating greater profits for farmers using Marketing Channel II. The inefficiency of the cayenne pepper marketing channel is evident in Channel I, which has a marketing efficiency of 4.38, while traders in Channel II also show inefficiency with a value of 1.91. Overall, Marketing Channel II demonstrates higher efficiency than Channel I, suggesting that higher efficiency values indicate less effective marketing channels.